Philanthropising Teacher Education? The Emerging Activities of Corporate Philanthropy in Teacher Development - Kurz, Benedict; Parreira do Amaral, Marcelo (Revista Española de Educación Comparada, 2022)
One crucial feature of the Global Education Industry (GEI) is its new mix of players. Within the GEI, corporate philanthropies have emerged as influential actors. They are increasingly involved in teacher education, in particular in the continuing professional development (CPD) of teachers which not only constitutes a new market, but also a policy instrument to disseminate ideas and beliefs. In this context, corporate philanthropies preferably collaborate with the state, for instance by forging public-private partnerships. Drawing on Anheier’s (2018) comparative approach, we explore the activities of Varkey Foundation (VF), a new edu-philanthropy, and Robert Bosch Foundation (RBF), a more traditional corporate philanthropy, in teacher CPD. Based on documents, we will apply a comparative perspective to explicate their purposes, approaches and roles, highlighting how both strive for change and, thus, engage in CPD. To conclude, we point out several implications for education policymaking, practice and future research.